Modern diagnostic and therapeutic approaches in familial maculopathy with reference to North Carolina macular dystrophy - Nekolova, Jana; Stepanov, Alexandr; Kousal, Bohdan; Stredova, Marketa; Jiraskova, Nada (Biomedical papers, 2022)
Aims. We present a familial hereditary macular dystrophy, resembling North Carolina Macular Dystrophy. In members of a family, we describe the development of diagnostic-therapeutic approaches and their impact on the prognosis of those whose vision was affected. Methods. The macular dystrophy of varying degrees of severity was diagnosed in 3 consecutive generations in different family members, both men and women. Modern therapeutic tools were used for the diagnostics. In one patient of the youngest generation, the development of secondary choroidal neovascularization (CNV) was identified and treated with an anti-VEGF (vascular endothelial growth factor) agent. DNA was isolated from venous blood and genome sequencing was performed in a proband. Results. We analysed the data of 13 members of one family of three consecutive generations. Six of them had macular dystrophy. The first were two of three siblings, a woman (73 years old) and a man (67). The offspring of the afflicted man, a female (36) and a male (80), had maculopathy. The first daughter of the woman (12) revealed findings of maculopathy but with normal electrical activity of the retina. The second girl (18), developed secondary CNV which responded well to intravitreal anti-VEGF treatment. Genetic analysis excluded mutations previously reported to be pathogenic for NCMD. Conclusion. If there is a maculopathy of unclear etiology in younger patients or in patients with unclear development or appearance, it is advisable to focus carefully on the family history and trace the occurrence of impaired vision in other family members.
Keywords: familial maculopathy; North Carolina Macular Dystrophy; anti-VEGF treatment